DIPLOMASI PERLINDUNGAN INDONESIA TERHADAP PEKERJA MIGRAN INDONESIA SEKTOR INFORMAL DI MALAYSIA TAHUN 2020-2022 - Ghania Maulaya Aisyah (2023)
The sending of Indonesian Migrant Workers abroad has been carried out since Indonesia had not yet gained its independence. At that time, sending Indonesian Migrant Workers abroad was only done individually and in a traditional way. One of the main destinations for Indonesian Migrant Workers is Malaysia. From year to year, the number of Indonesian Migrant Workers placements in Malaysia always ranks at the top. However, the high number of Indonesian Migrant Workers placements in Malaysia is also accompanied by the high number of complaints that come to the Indonesian representatives in Malaysia, especially in the informal sector. A number of problems, such as unpaid salaries, physical and verbal abuse, work that is not in accordance with the agreement, and unilateral dismissal, are often experienced by Indonesian Migrant Workers in the informal sector. Not to mention, the rampant sending of Indonesian Migrant Workers illegally also adds to the problems of Indonesian Migrant Workers in Malaysia. In this research, the author uses the framework of protection diplomacy. This research uses a descriptive qualitative approach and uses 2 (two) data sources, namely primary data and secondary data. The result of this research is that there are 3 (three) forms of diplomacy carried out to protect informal sector migrant workers in Malaysia: Formal/Core Diplomacy, Multi-stakeholder Diplomacy, and Informal Diplomacy. Through these actors, protection will continue to be intensified in order to realize effective and comprehensive protection for Indonesian Migrant Workers.